2021
DOI: 10.3390/ph14121218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnesium Orotate, Benfotiamine and a Combination of Vitamins on Mitochondrial and Cholinergic Function in the TgF344-AD Rat Model of Alzheimer’s Disease

Abstract: Glucose hypometabolism, mitochondrial dysfunction, and cholinergic deficits have been reported in early stages of Alzheimer’s disease (AD). Here, we examine these parameters in TgF344-AD rats, an Alzheimer model that carries amyloid precursor protein and presenilin-1 mutations, and of wild type F344 rats. In mitochondria isolated from rat hippocampi, we found reductions of complex I and oxidative phosphorylation in transgenic rats. Further impairments, also of complex II, were observed in aged (wild-type and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 58 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, ex vivo assessment of hippocampal mitochondria activity has shown that both 6‐to‐7‐month‐old and 15‐to‐16‐month‐old Tg rats display reduced capacity for oxidative phosphorylation and decreased complex I activity compared to WT controls. The older group in this study also displayed reduced complex II activity relative to age‐matched WT controls (Viel et al, 2021 ), further demonstrating the presence of mitochondrial dysfunction in this model of AD. Taken together with our data, these demonstrate that altered metabolism, both central and peripheral, is a noteworthy feature in this model of AD.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, ex vivo assessment of hippocampal mitochondria activity has shown that both 6‐to‐7‐month‐old and 15‐to‐16‐month‐old Tg rats display reduced capacity for oxidative phosphorylation and decreased complex I activity compared to WT controls. The older group in this study also displayed reduced complex II activity relative to age‐matched WT controls (Viel et al, 2021 ), further demonstrating the presence of mitochondrial dysfunction in this model of AD. Taken together with our data, these demonstrate that altered metabolism, both central and peripheral, is a noteworthy feature in this model of AD.…”
Section: Discussionsupporting
confidence: 67%
“…Transgenic rodent model of AD had lower maximal complex I and complex II respiration compared to wild type control and these differences were exacerbated with age. 43 In our study, Hartley guinea pigs did not have any age-related differences in maximal stimulated complex I (Figure 2C) or complex I and II (Figure 3D,E) respiration, contrary to our hypotheses. However, because this was the first investigation of age-related changes in guinea pig hippocampal mitochondrial function, we also made comparisons with the non-transgenic PET guinea pig that has less severe age-related changes in the brain.…”
Section: Key Point #1 Divergent Age-related Changes In Hippocampal Ad...contrasting
confidence: 93%
“…In our case, which is not a deficit model, we did not observe any improvement in ATP level, MPP, O 2 consumption or citrate synthase activity in SH-SY5Y-APP 695 cells ( Figure 4 ). In a study by Viel et al using a similar cocktail consisting of some of our compounds, the mitochondrial complex activity in a transgenic rat model was increased to that of wild type rats [ 28 ]. This effect is not found in our case, possibly due to the additional substances contained in the cocktail, which had been the decisive factor here.…”
Section: Discussionmentioning
confidence: 99%
“…A cocktail containing some of our tested compounds had a positive effect on AD symptoms in a TgF344-AD rat model. This could raise the mitochondrial function of the transgenic rats to the level of the wild-type rats [ 28 ]. Here, folic acid, magnesium-orotate and vitamin B6 in different combinations were tested in cellular and an invertebrate model of AD.…”
Section: Introductionmentioning
confidence: 99%